Consumer Acceptance of Toyota Hybrid Vehicles Amid Indonesia’s Transition Toward Battery Electric Vehicle - Chika Juliandini; Hasto Kristiyono (Community Engagement and Emergence Journal (CEEJ), 2026)
This study examines consumer acceptance of Toyota Hybrid Electric Vehicles (HEVs) amid Indonesia’s transition toward Battery Electric Vehicles (BEVs) on Indonesian market. Using a quantitative approach, the research analyzes six key variables: government incentives, infrastructure readiness, environmental concern, brand positioning, price perception, and after-sales service quality. Data were collected through an online Likert-scale questionnaire distributed to approximately 100 respondents selected via purposive sampling. The results indicate that four variables government incentives, price perception, brand positioning, and after-sales service quality significantly influence consumer acceptance of hybrid vehicles. Government incentives emerged as the strongest driver, suggesting that electrification policies positively impact hybrid perception. In contrast, infrastructure readiness and environmental concern were not significant, indicating that BEV-related external pressures have not yet substantially shifted consumer preferences. The findings highlight that Toyota’s hybrid strategy remains relevant due to strong brand trust, perceived value, and service reliability. However, its long-term competitiveness will depend on adapting to the evolving electrification landscape.